2008
DOI: 10.1128/aac.01101-07
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Toxicity of Colistin Methanesulfonate in Rats: Comparison of Various Intravenous Dosage Regimens

Abstract: The relative nephro-and neurotoxicity of colistin methanesulfonate (CMS) was investigated with rats during 7 days of intravenous administration in regimens mimicking twice-and once-daily dosing of a clinically relevant dose for humans. Histological examination revealed more-severe renal lesions with the regimen corresponding to once-daily dosing, indicating that the potential for renal toxicity may be greater with extended-interval dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 13 publications
4
53
0
1
Order By: Relevance
“…Kidney of control rat treated with saline for 7 days showing normal renal cortex and glomeruli (HE Â 100). in line with those of Wallace et al 18 who showed no significant change in pCr level after 30 mg/kg/12 h of colistin over 7days.…”
Section: Discussionsupporting
confidence: 80%
“…Kidney of control rat treated with saline for 7 days showing normal renal cortex and glomeruli (HE Â 100). in line with those of Wallace et al 18 who showed no significant change in pCr level after 30 mg/kg/12 h of colistin over 7days.…”
Section: Discussionsupporting
confidence: 80%
“…It is not known why the nephroprotective effect of melatonin against these drugs has not been examined clinically. A recent study in rats (37) reported that coadministration of N-acetylcysteine seemed to ameliorate CMS-induced oxidative stress in kidney cells; however, the daily dose of the prodrug, CMS, was very low based upon animal scaling considerations (48), and no differences in histological abnormalities were observed between groups, including the CMS group. Our study is the first to demonstrate the protective effect of melatonin against colistin-induced nephrotoxicity.…”
mentioning
confidence: 99%
“…Nephrotoxicity rates in patients receiving currently recommended CMS dosage regimens are often ϳ45 to 55% (8,10,11,14,19,20,22). Although the mechanism of colistin-induced nephrotoxicity still remains unknown, it appears to be related to total dose of CMS and duration of therapy and is usually reversible upon cessation of therapy (14,48). Notwithstanding its reversibility, nephrotoxicity is currently a major dose-limiting adverse effect impacting the clinical use of CMS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Los autores proponen la primera fórmula para calcular la dosis de carga (basada en el peso corporal) y de mantención (que incorpora el aclaramiento de creatinina), además de hacer recomendaciones para pacientes en hemodiálisis intermitente y en terapias continuas de sustitución renal. Los autores, además, sugieren que la administración de CMS sea en tres dosis en pacientes con función renal normal, lo que se asociaría a menor toxicidad en modelos animales 41 , y a menor emergencia de resistencia en estudios in vitro 42 . Si aceptamos la recomendación de Garonzik y cols 40 , el objetivo plasmático de colistín a alcanzar es 2,5 mg/L, algo así como un punto intermedio entre eficacia y toxicidad.…”
Section: Farmacocinética-farmacodinámica (Pk/pd)unclassified